2015
DOI: 10.1016/j.ijgo.2015.06.041
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to early prenatal care in South Africa

Abstract: Synopsis: Current barriers to early prenatal care in South Africa include poor pregnancy planning, fear of HIV-related stigma, and cultural perceptions and superstitions. ABSTRACTObjective: To understand the barriers delaying early prenatal care for women in South Africa.Methods: A mixed-methods study was conducted at a center in Pretoria. Conclusion: Significant efforts should be devoted to improving access to contraception and prepregnancy counseling in order to improve early prenatal care attendance. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 17 publications
2
28
1
Order By: Relevance
“…Other studies [39,40] showed that women do not attend ANC because they are not familiar OR Odds ratio, CI Confidence interval a statistically significant at 1% level of significance, b significant at 5% level of significance c All estimates (OR, CI) are weighted using sampling weights, sampling unit and strata available in the 2014-15 DHS data or do not understand the value of ANC especially those who did not experience any complications in their prior pregnancy or those whose pregnancy is their first (primigravida). Contrary to previous findings on ANC utilization [22,41,42], age and wealth group were not significantly associated with the outcome in our analysis. However, we kept these variables in the model based on a priori knowledge [41] and included the interaction term between these two variables in the model for sensitivity analysis.…”
Section: Demographic and Socio-economic Status Factorscontrasting
confidence: 99%
See 2 more Smart Citations
“…Other studies [39,40] showed that women do not attend ANC because they are not familiar OR Odds ratio, CI Confidence interval a statistically significant at 1% level of significance, b significant at 5% level of significance c All estimates (OR, CI) are weighted using sampling weights, sampling unit and strata available in the 2014-15 DHS data or do not understand the value of ANC especially those who did not experience any complications in their prior pregnancy or those whose pregnancy is their first (primigravida). Contrary to previous findings on ANC utilization [22,41,42], age and wealth group were not significantly associated with the outcome in our analysis. However, we kept these variables in the model based on a priori knowledge [41] and included the interaction term between these two variables in the model for sensitivity analysis.…”
Section: Demographic and Socio-economic Status Factorscontrasting
confidence: 99%
“…Employment status was a protective factor from inadequate ANC visits which is consistent with previous findings [21]. Women who are employed might be more informed and have financial autonomy to access health care compared to unemployed women as many other studies have reported [4,21,42].…”
Section: Demographic and Socio-economic Status Factorssupporting
confidence: 89%
See 1 more Smart Citation
“…Although reasons for poor access were not assessed, likely factors include stigma (real or perceived), and concomitant disrespect and abuse meted out by health workers [3234]. The especially low levels of attendance at HCHC, the Hillbrow site, where most residents are foreign nationals [35], suggests that xenophobia within the health system might be deterring women who are not South African from seeking health care [36, 37].…”
Section: Discussionmentioning
confidence: 99%
“…It is widely acknowledged that access to biomedical health care remains elusive to many patients, especially the poor and rural dwellers in Ghana and the subregion (Aikins & Marks, 2007;Helmchen & Lo Sasso, 2010;Powell-Jackson, Hanson, Whitty, & Ansah, 2014). Scholars and researchers criticize the structure of biomedical care, and opine its inability to reach the mass is due to social distance, economic and financial constraints, and the uneven distribution of health and medical resources in this part of the world (Haddad, Makin, Pattinson, & Forsyth, 2015;Harris et al, 2011;Jørgensen, 2008;Kissah-Korsah, 2008;Mills et al, 2012). For instance, research in the 1980s and early 1990s observed a drastic fall in the use of biomedical care among Ghanaians due to the introduction of user fees during the structural adjustment era (Anyinam, 1994;Asenso-Okyere et al, 1998;Nyonator & Kutzin, 1999).…”
Section: A Triple-systems Model Approach To Medical/health Pluralism mentioning
confidence: 99%